2013
DOI: 10.1007/s12311-013-0482-y
|View full text |Cite
|
Sign up to set email alerts
|

Triple Therapy with Darbepoetin Alfa, Idebenone, and Riboflavin in Friedreich’s Ataxia: an Open-Label Trial

Abstract: Minimal objective evidence exists regarding management of Friedreich's ataxia (FRDA). Antioxidant and recombinant human erythropoietin therapies have been considered potential treatments to slow progression of FRDA in a small number of studies. The primary objective of the current study was to test the efficacy, safety, and tolerability of triple therapy-darbepoetin alfa, idebenone, and riboflavin-in FRDA in a clinical pilot study. Patients included in this study were nine females, 16 to 45 years of age (avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…LVMI decreased between 8.3 and 21.8 g/m 2 and LVEF decreased between 3.6 and 7.5%. Triple therapy yielded cardiac stability in participants during the 4 years of treatment [57]. …”
Section: Combination Therapymentioning
confidence: 99%
“…LVMI decreased between 8.3 and 21.8 g/m 2 and LVEF decreased between 3.6 and 7.5%. Triple therapy yielded cardiac stability in participants during the 4 years of treatment [57]. …”
Section: Combination Therapymentioning
confidence: 99%
“…Considering that the effect of idebenone alone might be unremarkable, a small open study including nine patients with FRDA investigated the effect of triple therapy of idebenone 10-20 mg/kg/ day, riboflavin 10-15 mg/kg/day, and 150 μg darbepoetin alfa every 2-3 weeks for 32±19.4 months. Although there was no improvement in ataxia during the first months, a small decrease in disease progression during the following 2 years of treatment was observed [72].…”
Section: Idebenonementioning
confidence: 85%
“…Although some data demonstrated reduced iron accumulation in DN evaluated by apparent transverse relaxation rate on MRI study, no neurological improvement was observed [75]. In addition, Arpa et al studied a combined therapy with deferiprone, idebenone, and riboflavin and showed an uncertain benefit in cardiac hypertrophy and no neurological improvement [72] [56].…”
Section: Deferipronementioning
confidence: 99%
“…It is a potent antioxidant 50 and can donate electrons to complex III of the electron transport chain. This drug has also found utility in studies on mitochondrial diseases including Friedreich’s Ataxia 51 and is approved in Europe for Leber’s Hereditary Optic Neuropathy 52 . It is therefore possible that idebenone, while exhibiting only weak activity on Mtb whole cells, could have potential for repurposing against additional diseases as well.…”
Section: Discussionmentioning
confidence: 99%